Impacts of moisture supply from the subtropical western Pacific on the subtropical high and the atmospheric river during the heavy rain of 2020 in Japan - Zhao, Ning; Manda, Atsuyoshi; Guo, Xiaojun; Wang, Bin (Frontiers in Earth Science, 2022)
Our recent study suggested that moisture from the subtropical western Pacific (WP) contributed the most to an atmospheric river (AR) event and the related heavy rainfall during the heavy rain of 2020 in Japan based on a Lagrangian approach. However, the actual role of moisture from the subtropical WP region in the AR and heavy rain formations remains unclear. To evaluate that, we conducted a set of numerical sensitivity experiments by adjusting the surface moisture supply over the subtropical WP region with factors of 0%, 50%, and 200%. The sensitivity experiments suggest that the reduced surface evaporation over the subtropical WP suppressed the local convective activity and decreased moisture content in the whole troposphere, leading to shallow and weak positive geopotential height anomalies. Although the slightly strengthened WP subtropical High (WPSH) and related anomalous anticyclonic circulation enhanced the southwesterly wind, convective activities along the Meiyu-Baiu front were still weakened due to the largely reduced moisture supply, resulting in another anomalous anticyclonic circulation over Japan but had much stronger and deeper structures. These two anomalous circulations and the reduced moisture modulated the AR over Japan, which eventually caused the weakened rainfalls and the northward migration of the rainband. By contrast, larger surface evaporation enhanced the local convective activities and weakened the dominant WPSH, resulting in the weakening and the southward migration of the AR. Overall, this study confirmed the large contributions of moisture supply from the subtropical WP region to the AR and related precipitation over Japan during the record-breaking Meiyu-Baiu season in 2020 via both dynamic and thermodynamic influences. In addition, it reveals that, although larger evaporation over the WP region would increase the total rainfalls but would not have led to more several rainfalls over certain regions, such as the relatively small Kyushu Island.